Synthesis of ZSM-5 zeolite with small crystal size and its catalytic performance for ethylene oligomerization - Yamamura, M.; Chaki, K.; Wakatsuki, T.; Okado, H.; Fujimoto, K.
ZSM-5 zeolites of SiO2 Al2O3 = 25 with a small crystal size were synthesized under various conditions in order to clarify a relationship between external surface area and catalytic performance, especially lifetime, for the oligomerization of ethylene to higher hydrocarbons of the gasoline range. The measurement of the external surface area, XRD patterns, and FTi.r. spectra of the resulting ZSM-5 zeolites suggested that their crystal grains were very fine. The shapes and sizes of the primary grains of the ZSM-5 zeolites were observed by means of a scanning electron microscopy with a magnification of 300,000. The crystal sizes were in the range of 30-50 nm. In the oligomerization of ethylene, a proton-type zeolite that was synthesized under a high molar ratio of OH SiO2 showed both high ethylene conversion and high gasoline range selectivity for three times longer on-stream time than those of other zeolites. The external surface area of the zeolite was also three times greater than those of other zeolites, which indicated that the lifetime of ZSM-5 zeolite in the oligomerization of ethylene depended on the external surface area or crystal size.
Keywords: CATALYST SELECTIVITY; CRYSTAL STRUCTURE; CRYSTALLIZATION; CRYSTALS; ETHYLENE; GRAIN SIZE AND SHAPE; HYDROCARBONS; SCANNING ELECTRON MICROSCOPY; SURFACE MEASUREMENT; SYNTHESIS (CHEMICAL)